2019
DOI: 10.1186/s13046-019-1196-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-EMT properties of CoQ0 attributed to PI3K/AKT/NFKB/MMP-9 signaling pathway through ROS-mediated apoptosis

Abstract: Background Breast cancer is the most prevalent cancer among women. In triple-negative breast cancer (TNBC) cells, a novel quinone derivative, coenzyme Q 0 (CoQ 0 ), promotes apoptosis and cell-cycle arrest. This study explored the anti-epithelial–mesenchymal transition (EMT) and antimetastatic attributes of CoQ 0 in TNBC (MDA-MB-231). Methods Invasion, as well as MTT assays were conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 61 publications
4
77
0
Order By: Relevance
“…The results were consistent with previous reports that esophageal cancers cells with EMT growth pattern exhibited more resistance to chemotherapeutic drugs [34,35]. It has been reported that Anti-EMT properties could promoted apoptosis [36]. As the critical regulators of apoptosis, BCL-2 family proteins are also correlated with chemoresistance [37,38].…”
Section: Discussionsupporting
confidence: 92%
“…The results were consistent with previous reports that esophageal cancers cells with EMT growth pattern exhibited more resistance to chemotherapeutic drugs [34,35]. It has been reported that Anti-EMT properties could promoted apoptosis [36]. As the critical regulators of apoptosis, BCL-2 family proteins are also correlated with chemoresistance [37,38].…”
Section: Discussionsupporting
confidence: 92%
“…These data indicated that treatment of HASMCs with IS induced the activated of PI3K/Akt signaling pathway. As NF‐κB is a transcription factor and its activation could be in part regulated by the upstream pathway of PI3K/Akt (Yang et al, ), we measured the phosphorylation of NF‐κB p65 protein level under the presence of LY294002 stimulation with IS. As shown in Figure c, IS significantly activated the phosphorylation of NF‐κB p65, whereas the presence of LY294002 reversed the activated effect of IS on the phosphorylation of NF‐κB p65.…”
Section: Resultsmentioning
confidence: 99%
“…4A. Although differentially expressed circRNAs have been proposed to be closely associated with EMT (12,15), the roles of circRNAs in breast cancer EMT remain unclear. The present study aimed to identify novel circRNAs that regulate EMT of breast cancer cells.…”
Section: Go and Kegg Analysis Of Differently Expressed Circrnasmentioning
confidence: 99%
“…cORM-A1 and dETA/NO combination therapy showed antimetastatic action and resulted in normalization of endothelial metabolism, diminution of platelet activation, and inhibition of EMT progression (12). coenzyme Q 0 attributed to the phosphatidyl inositol 3 kinase (PI3K)/protein kinase B (AKT)/nuclear factor (NF)κB/matrix metalloproteinase-9 signaling pathway through reactive oxygen species-mediated apoptosis can inhibit the progression of metastasis as well as EMT (in vitro and in vivo) (15). Metastasis of breast cancer remains challenging for the current clinical treatments and more than half of the patients suffer from a disease relapse due to distant metastases (16).…”
Section: Introductionmentioning
confidence: 99%